Vegetation Diversity in the Mangrove Ecosystem of Jorong District, Tanah Laut Regency - Hartanto, Delon Tri; Putra, Guruh Mayka; Rizalli, Akhmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Mangrove ecosystems play a crucial role in maintaining coastal environmental stability and supporting biodiversity in tropical regions. This study aims to analyze the diversity, structure, and dominance of mangrove vegetation in Jorong District, Tanah Laut Regency, South Kalimantan, as a scientific basis for sustainable mangrove management. The research was conducted in September 2025 in the mangrove forests of Muara Asam-Asam and Swarangan Villages using a purposive sampling method combined with transect plots. Vegetation data were collected at three growth levels, namely seedlings, saplings, and trees, through nested plots of different sizes. Vegetation analysis included species density, relative density, frequency, relative frequency, Important Value Index (IVI), and species diversity using the Shannon-Wiener index. The results showed that three mangrove species were identified, namely Avicennia marina, Rhizophora apiculata, and Sonneratia alba. Avicennia marina was the most dominant species across all forest density categories, as indicated by its high IVI values. The Shannon-Wiener diversity index revealed moderate diversity in high-density mangrove forests (H’ = 1.09) and lower diversity in medium (H’ = 0.66) and low-density forests (H’ = 0.63). These variations are influenced by habitat conditions and anthropogenic pressures such as land conversion and logging activities. Overall, the mangrove ecosystem in Jorong District still exhibits sufficient ecological diversity but requires sustainable management to prevent further degradation and ensure long-term ecosystem stability.